From Homeland to Hybrid Space: Tracing Diaspora and Cultural Modernity in the Novels of Onoura Nzekwu - Smita Rajshekhar Patil (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2026)
This present research attempts to analyse, interpret and elaborate the possibilities and conflicts of cultural modernity and proto-diasporic identity among Igbo people who are torn between Western influences and traditional customs in Onuora Nzekwu’s novels Blade Among the Boys and Wand of Noble Wood. This study explores the argument that Nzekwu imagines a hybrid space where identity is negotiated, fragmented, and reconstructed rather than merely lamenting the loss of tradition or completely adopting Western modernity. To elaborate this, he uses themes like religion, marriage customs, kinship, education, and moral agency. The study also depicts how Nzekwu illustrates the transition from homeland rootedness to cultural displacement and return using his characters, narrative structure, and cultural symbolism. It also exhibits how the hybridity between the two disorders and enhances identity. The study concludes by arguing that Nzekwu’s novels foreshadow later diasporic literatures in Africa by depicting the psychological and moral costs of migration (whether internal, spiritual, or cultural) and by providing strategies for finding meaning in tradition reimagined in modern ways.